2011
DOI: 10.1177/0300985811398248
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic and Ultrastructural Studies on Experimental Caprine Besnoitiosis

Abstract: The distribution pattern and associated tissue reactions with progressive changes in Besnoitia caprae cysts were investigated in 6 experimentally infected 16-to 20-month-old male goats. Each goat was subcutaneously inoculated with approximately 13 Â 10 8 B caprae bradyzoites. The animals were examined daily for development of clinical besnoitiosis, and skin biopsies from distal parts of the limbs were taken at weekly intervals. At 15, 30, 60, 120, 180, and 365 days postinfection (DPI), 1 goat was euthanized. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In the literature, nomenclature regarding the composition of Besnoitia tissue cysts and cysts walls is not consistent. None of the published schemes 13,26,41,42 were fully applicable when looking at B. besnoiti tissue cyst development in this study. Therefore, a new nomenclature that is fully applicable to B. besnoiti tissue cysts is suggested: structures within the host cell are called by their respective name—that is, bradyzoites, parasitophorous vacuole, membrane of the parasitophorous vacuole, host cell cytoplasm including organelles and nuclei, and host cell membrane.…”
Section: Discussionmentioning
confidence: 96%
“…In the literature, nomenclature regarding the composition of Besnoitia tissue cysts and cysts walls is not consistent. None of the published schemes 13,26,41,42 were fully applicable when looking at B. besnoiti tissue cyst development in this study. Therefore, a new nomenclature that is fully applicable to B. besnoiti tissue cysts is suggested: structures within the host cell are called by their respective name—that is, bradyzoites, parasitophorous vacuole, membrane of the parasitophorous vacuole, host cell cytoplasm including organelles and nuclei, and host cell membrane.…”
Section: Discussionmentioning
confidence: 96%
“…No relevant studies are available regarding Besnoitia infection of rams. Nevertheless, experimental work performed in bucks has indicated that Besnoitia caprae can affect their genital system, with cysts of the protozoon identified in the testicular parenchyma and the scrotum (Oryan et al, 2011). Other clinical studies have indicated that Besnoitia besnoiti can affect the testicular parenchyma and scrotum of bulls (Sekoni et al, 1992;Dubey et al, 2013), leading to reduced libido and suboptimal semen quality, although in subsequent studies the protozoon could not be detected in the semen of affected bulls (Esteban-Gil et al, 2014).…”
Section: Testicular Functionmentioning
confidence: 99%
“…According to Njagi et al (1998) , Besnoitia infections are of economic importance, associated with high morbidity and low mortality in their hosts ( Glover et al, 1990 ; Van Heerden et al, 1993 ). The disease affects a wide range of domestic and wildlife host species ( Schulz, 1960 ; Njagi et al, 1998 ), and infections present in three distinct stages: the acute anasarca stage, subacute stage and the chronic scleroderma stages which involves the development of cysts predominantly in the superficial tissues ( Bigalke, 1968 ; Basson et al, 1970 ; Oryan et al, 2011 ; Langenmayer et al, 2015 ). Clinical cases are also characterised by physical features such as the formation of cysts in the connective tissues of the skin, muscles and other organs of their hosts, as well as the thickening of the skin around the eyes, face, nose, scrotum and the limbs ( Njagi et al, 1998 ; Schulz, 1960 ).…”
Section: Introductionmentioning
confidence: 99%